Metagenomic Insights into Coal Slag Remediation Effects on Soil and Microbial Health in Qinghai’s Muli Coal Mine - Qi Lin; Pan Yang; Yongbei Zhang; Wenfei Zhang; Hongping Wu (Microorganisms)
Long-term coal mining in the Muli coal mine area of Qinghai Province has degraded soil quality and reduced microbial diversity, making it imperative to implement effective ecological restoration measures to restore soil quality and enhance ecosystem functions. This study evaluated soil samples under 11 ecological restoration treatments using metagenomic sequencing combined with soil quality analysis to explore the responses of the microbial community structure and function to identify effective restoration measures. This study demonstrated that ecological restoration significantly increased the soil microbial diversity and richness, with the MLII1 (soil samples treated with a chemical weathering agent, attapulgite, and a microbial agent) and MLIII1 (soil samples treated with sheep manure (2.4 kg/m2), granular organic fertilizer (1.2 kg/m2), and the microbial agent) treatment groups performing exceptionally well. Further analysis of the functional networks revealed that although the MLII2 (soil samples treated with the chemical weathering agent and attapulgite) treatment group did not exhibit the highest species diversity, it exhibited the highest functional network complexity. The results of hierarchical clustering analysis showed that the microbial community of the MLII2 treatment group was most similar to that of the natural meadows compared to the other treatment groups. From the perspective of overall ecological restoration, this study concluded that the MLII2 treatment group exhibited the most favorable ecological restoration outcomes. This finding emphasizes the importance of not only enhancing microbial diversity but also prioritizing the restoration of community functions, especially for the recovery of fragile high-altitude ecosystems.